Sosialisasi Cara Praktis Belajar Bahasa Inggris kepada Siswa SMK Negeri 1 Dolo Barat - Said, Mawardin M; Rita, Ferry; Budi, Budi; Wardatun Islamiyah, Ibmasiah; Mawardin, Ilmuislami; Aisyah Al Munawwaroh, Sitti; Ilmiah, Ide (Universitas Negeri Surabaya, 2025)
This Community Service aims at socializing Practical Ways of Learning English to students of SMKN (Sekolah Menengah Kejuruan Negeri, Government Vocational High School) 1 West Dolo. They hopefully can apply them in learning English especially increasing their English vocabulary so that they can make sentences and communicate in the foreign language. They were motivated to master English used to communicate in the international language practically. Its specific traget was the students who had spirits to learn English especially to add their English vocabulary so that they they can to use it constantly and influence their frients in using the English vocabulary in sentences. They will then be easy to communicate in the global language. They also can be global learners. Communicative method is used to reach the objecive. Its result hopefully that through this Socialization the students can use English in simple sentences. The Practical Ways of Learning English explained and trained to them can be applied by them even though they have not been able to be fluent in constructing and expressing the English sentences. They hopefully can use the English even though have not mastered it yet. This Article is outcome of the Community Service.